A successful attenuation of Postherpetic neuralgia using low-level laser therapy: A retrospective study - Wirya, Andrew Yoshihiro; Karmila, I Gusti Ayu Agung Dwi; Wirya, Stephen; Mahariski, Pande Agung (Journal of Pakistan Association of Dermatologists, 2023)
Objective This study aims to determine the efficacy of Low-level laser therapy (LLLT) in PHN patients. Methods A retrospective study from January 2019 – December 2021. Thirty-four patients with Postherpetic neuralgia were included in this study. This study used a 660-nm wavelength LLLT HLA-2000 (HANIL, Korea), an aluminium-gallium-arsenide (AlGaAs) diode laser in a continuous wave scanning setting with a 15-mW power and applied for 15 minutes for each area. All patients were given 16 sessions for eight weeks. Pain score was obtained using a numerical pain rating scale (NPRS). Results All patients in this study experienced significant pain reduction after therapy. The mean starting NPRS was 8.26±1.31, by the fourth week NPRS was reduced to 4.65±0.98, and the eighth week NPRS was at 1.74±1.33. Conclusion Postherpetic neuralgia poses a challenge for both the patient and physician due to its refractory and chronic nature. LLLT is an effective, low-cost, and safe alternative treatment for patients with Postherpetic neuralgia, especially those with contraindications or who have used multiple medications.